Atlantic cod (Gadus morhua) assessment approaches in the North and Baltic Sea: A comparison of environmental DNA analysis versus bottom trawl sampling - Kasmi, Yassine; Blancke, Tina; Eschbach, Erik; Möckel, Benita; Casas, Laura; Bernreuther, Matthias; Nogueira, Pedro; Delfs, Gertrud; Kadhim, Samira; Meißner, Timo; Rödiger, Marcellus; Eladdadi, Amina; et al. (Frontiers in Marine Science, 2023)
The assessment of fish stocks is often dependent on scientific trawl fisheries surveys, which are both invasive and costly. The analysis of environmental DNA (eDNA) from water samples is regarded as a non-invasive and cost-effective alternative, but meaningful performance evaluations are required for a wider application. The goal of this study was to comparatively analyze a newly developed, more sensitive real-time PCR based eDNA approach with bottom trawl fisheries catches to locally detect and quantify Atlantic cod (Gadus morhua) in the North and Baltic Seas. With a species-specificity of the qPCR assay of 100%, a minimal limit of 15 Cytochrome b eDNA copies was determined for the detection of cod. In addition, a Gaussian processing regression proved a significant correlation (95%) between eDNA (copies per L of water) and cod biomass (CPUE/Ha) found by bottom trawling. The results presented here prove the potential of eDNA analyses for quantitative assessments of commercial fish stocks in the open ocean, although additional comparative analyses are needed to demonstrate its performance under different oceanographic conditions.